Philadelphia chromosome and FISH- negative, cryptic BCR/ABL1 positive acute myeloid leukaemia: A diagnostic dilemma - Abdul Halim, Sarah; A.Talib, Norlelawati; Mohd Nasiruddin, Dhamirah Nazihah (2022)
Introduction: Acute myeloid leukaemia (AML) with BCR/ABL1 is a provisional entity classified in the most recent WHO classification of AML with recurrent genetic abnormalities. This entity can pose diagnostic dilemmas as it can be confused with blastic phase of chronic myeloid leukamia (CML) or mixed phenotype acute leukaemia (MPAL) with BCR-ABL1. We present here a patient with Philadelphia chromosome negative AML and BCR/ABL1 fusion detected by PCR.